Attitudes towards hedging by diversified and non-diversified farmers - Eke-Göransson, Charlotte; Rinman, Magnus (2012)
Deregulation on the market for agricultural products leads to a more globalised market with increasing price fluctuations. This, in turn, places the farmer in positions influenced by new risks but also improved opportunities. The farmers are faced by uncertainty in terms of financial outcome. To be able to utilise these new market conditions it becomes increasingly important for farmers to continuously follow the price trend, and to develop strategies how to manage the risks exposed by a volatile market.